PENERAPAN METODE PEMBELAJARAN BEACH BALL (BOLA PANTAI) DALAM KETERAMPILAN BERBICARA BAHASA JERMAN SISWA - Tahmi Tahmi; Nurming Saleh (Makassar State University, 2018)
This research is a classroom action research which aims to find out the planning, process, and results of beach ball learning methods in students' German speaking skills. The research data consists of two types, namely: qualitative data and quantitative data. Qualitative data is obtained through observation, and quantitative data is obtained through the first cycle and second cycle speaking skills tests. Data were analyzed using percentage techniques. The results showed that speaking skills with the percentage of grades obtained by students in the first cycle reached 60.66%, and the second cycle reached 78.25%. These results indicate that the application of the beach ball learning method increases in students' German speaking skills